2012
DOI: 10.3171/2012.5.jns1271
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the optic nerve sheath subarachnoid space in patients with intracranial hypotension syndrome

Abstract: Disappearance of the CSF space in the ONS was frequently observed in patients with SIH. This characteristic finding may be useful in the diagnosis of SIH as well as in the evaluation of treatment effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The cardinal finding is increased intracranial blood volume [35]. Characteristic MRI findings are thickened pachymeninges with contrast enhancement, subdural fluid collections, engorged cerebral veins, rounded dural sinuses, brain sagging, disappearance of the CSF space of the optic nerve sheath and an inferiorly displaced midbrain [35, 36]. These findings are also useful in the follow-up period after treatment.…”
Section: The Role Of Mri In Other Csf Disordersmentioning
confidence: 99%
“…The cardinal finding is increased intracranial blood volume [35]. Characteristic MRI findings are thickened pachymeninges with contrast enhancement, subdural fluid collections, engorged cerebral veins, rounded dural sinuses, brain sagging, disappearance of the CSF space of the optic nerve sheath and an inferiorly displaced midbrain [35, 36]. These findings are also useful in the follow-up period after treatment.…”
Section: The Role Of Mri In Other Csf Disordersmentioning
confidence: 99%
“…The optic nerve sheath is distensible in the retrobulbar region. Clinical and experimental studies in people and monkeys have shown that increases in intracranial pressure cause measurable increases in the optic nerve sheath diameter . Furthermore, optic nerve sheath diameter measurements are highly reliable in people when using magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…Findings on spinal MRI are as follows: distention of the epidural veins (78%), epidural fluid collection (89% of patients) (Fig. It does not denote the site of CSF leakage (false localizing C1/C2 sign) [66,67]. The C1/C2 sign -high signal intensity between the spinous processes of C1 and C2 -is present in 33-67% of patients [70][71][72][73].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%